Effects of Technological Developments on Industrial Training - Jain, Abhay; Chandwani, M. (Journal of Engineering Education Transformations, 1992)
Engineering education is characterised by several aspects which make it different from other educational disciplines. One of these is based on the fact that training and placement has to be an integrated component of the engineering education. In this paper, we highlight the increased importance of training in this fast developing technological world. An appropriate training makes a candidate suitable for placement in industries and other organizations. Most of the training and placement cells of the engineering colleges of the country are lacking in fulfilling their needs for one reason or another and in turn affecting the over all performance of their institutions. The tradition in our industrial development in last forty five years of freedom has remained unchanged. Total, when technological developments have caused opening of several new issues, the relations between industries and educational institutions require a fresh look. There is a need to have different and better understanding between these two. Of course, problems exist, but sooner the better, we will have to establish a system which can last for long. The system should be able to bear the pressure of fast technological growth and catre to the needs of future growth. In our views, the educational institutions can take initiatives in this regard. If steps are taken with a broader view in the mind, there should not be any dought about the hopeful and better results. In this paper, we are also describing the activities which can be taken up by educational institutions as well as industrial organizations.